2020
DOI: 10.5489/cuaj.6661
|View full text |Cite
|
Sign up to set email alerts
|

A drug-coated balloon treatment for urethral stricture disease: Two-year results from the ROBUST I study

Abstract: Introduction: Mechanical balloon dilation and direct visualization internal urethrotomy (DVIU) are the most widely used treatments for urethral stricture disease in the U.S., but recurrence rates are high, especially after re-treatment. This study investigates the safety and efficacy of the Optilume™ paclitaxel-coated balloon for the treatment of recurrent strictures. Methods: Men with recurrent bulbar strictures ≤2 cm with 1–4 prior endoscopic treatments were treated with the Optilume™ drug-coated ballo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The recent and ongoing ROBUST trials have introduced a paclitaxel-coated balloon system, now FDA-approved in the USA, and have demonstrated their safety and efficacy for the treatment of urethral stricture disease [ 7 , 8 ]. In light of the introduction of this novel balloon system, we sought to establish a fundamental clinical baseline by evaluating our experience with “traditional” BD.…”
Section: Introductionmentioning
confidence: 99%
“…The recent and ongoing ROBUST trials have introduced a paclitaxel-coated balloon system, now FDA-approved in the USA, and have demonstrated their safety and efficacy for the treatment of urethral stricture disease [ 7 , 8 ]. In light of the introduction of this novel balloon system, we sought to establish a fundamental clinical baseline by evaluating our experience with “traditional” BD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications of phase I/II studies have shown that men treated with Optilume have a functional success rate of 70% at 2 years. 15 Results of a phase III, single-blind, randomized, controlled trial of Optilume vs standard endoscopic therapy are reported here.…”
mentioning
confidence: 99%
“…Functional success in this study was based on improvement in IPSS and had similar rates at 2 and 3 years (68% and 67%, respectively). 8 The reduction in IPSS by an average of 72% (19.7 points) was considered clinically meaningful through 3 years post-treatment for a population with moderate-to-severe symptoms at baseline. 9 Significant improvements were also observed in voiding function, with average Qmax remaining >15 mL/sec at all follow-up visits through 3 years.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Based on the study design, cystoscopy was not performed after 1 year, however functional success occurred in 70% (32/46) at 2 years, defined as International Prostate Symptom Score (IPSS) improvement ≥50% in the absence of retreatment need. 8 We now report the 3-year safety and efficacy outcomes of the ROBUST I trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation